2017
DOI: 10.1111/idj.12263
|View full text |Cite
|
Sign up to set email alerts
|

Risk of osteoporosis in elderly individuals attending a dental clinic

Abstract: Our findings reveal that most elderly female patients visiting the dental clinic had a high risk of osteoporosis and a low BMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
5
1
2
Order By: Relevance
“…Lee et al [ 25 ] concluded that simple visual estimation of the mandibular inferior cortex width on panoramic radiographs might be useful for identifying postmenopausal women with low BMD. In similar studies Ohtsuki et al, [ 26 ] as well as Horner and Devlin [ 27 ] also found that mandibular cortical width significantly correlated with BMD,.…”
Section: Discussionmentioning
confidence: 73%
“…Lee et al [ 25 ] concluded that simple visual estimation of the mandibular inferior cortex width on panoramic radiographs might be useful for identifying postmenopausal women with low BMD. In similar studies Ohtsuki et al, [ 26 ] as well as Horner and Devlin [ 27 ] also found that mandibular cortical width significantly correlated with BMD,.…”
Section: Discussionmentioning
confidence: 73%
“…Simple correlation coefficients between the MCW and skeletal BMD were between 0.23 (weak) and 0.68 (moderate). Significant correlation was observed between the MCW and skeletal BMD in older women but not in older men in one study [48]. Only one study, which focused on Japanese younger adults, reported a significant association between the MCW and osteoporosis as determined by ultrasound in younger men, but not in younger women [36].…”
Section: Usefulness Of the Mcw In Screening For Osteoporosismentioning
confidence: 90%
“…A identificação precoce de indivíduos com baixa densidade e qualidade óssea associado ao distúrbio osteometabólico é importante para estabelecer estratégias na prevenção de fraturas. Dessa forma, vários estudos (CALCIOLARI et al, 2015;GEARY et al, 2015;KAVITHA et al, 2015;KIM et al, 2016;YAMADA et al, 2015;MILIUNIENE et al, 2016;MURAMATSU et al, 2016;CARMO, MEDEIROS, 2017;HWANG et al, 2017;OHTSUKI et al, 2017;SPEZZIA et al, 2017;KINALSKI et al, 2020)…”
Section: Metodologiaunclassified